Association between periventricular hyperintensity or deep white matter hyperintensity and outcomes of patients with ischemic stroke - Hongwei Ren; Du Wang; Xing Wang; Jinlong Wu; Junli Huang; Honghua Jin; Chengfang Huang; Lei Lei (Frontiers in Neurology, 2025)
IntroductionThis study investigates the association between white matter hyperintensities (WMH), specifically periventricular hyperintensity (PVH) and deep white matter hyperintensity (DWMH), and the prognosis and recurrence risk in patients with ischemic stroke.MethodsA retrospective analysis was conducted on 278 patients with acute ischemic stroke, including 112 with PVH and 166 with DWMH. Key outcome measures included functional outcome (modified Rankin Scale score), mortality, neurological recovery, and stroke recurrence at 3, 6, and 12 months after treatment.ResultsSevere PVH was significantly associated with unfavorable functional outcomes at 3, 6, and 12 months, while severe DWMH was only linked to unfavorable outcomes at 3 months. Mild PVH, but not DWMH, was associated with neurological recovery. Both higher PVH and DWMH were significantly correlated with stroke recurrence, with PVH showing an association at 12 months and DWMH at all time points. Severe PVH, but not DWMH, was also associated with stroke-related deaths.DiscussionThese findings highlight the significant prognostic value of PVH and DWMH subtypes in ischemic stroke, suggesting their potential utility in predicting long-term functional outcomes, recurrence, and mortality.